Akuntabilitas Pengelolaan Alokasi Dana Desa (ADD) di Desa – Desa Kecamatan Rogojampi Kabupaten Banyuwangi - Siti Ainul Wida; Djoko Supatmoko; Taufik Kurrohman (UPT Penerbitan Universitas Jember, 2017)
This study focuses on the application of accountability system, which is a form of responsibility over the management of public funds by the Government which was done starting from the planning stages, execution, implementation, and surveillance of the management of village Funds Allocation. This study was conducted because of the amount of the funds allocated for rural development as well as susceptible to fraud resulting from the lack of transparency of reporting to the public, as well as the performance of the implementation Team in the village of accountable reporting accountability that has not been in accordance with the applicable regulations. This study is expected to be beneficial to the Government of Banyuwangi Regency especially Rogojampi Sub-district in an attempt to improve the accountability of the management of the village Funds Allocation. This study was conducted in nine villages in Rogojampi sub-district. The Data collected by direct observation in the villages and with interviews with the parts of County, district monitoring teams, Treasurer of villages, village of Consultative Body Elements, as well as representatives of the villagers. This study shows that in the planning and the execution were in accordance with the applicable pr,ocedures and operations have been conducted in a transparent and accountable. For the surveillance phase is still not going well because of lack of transparency towards the public. As for the implementation phase also has not run properly due to human resources managing team in making the Administration report is still lacking, so the necessary existence of coaching and supervision over local government.Keywords: Accountability, Transparency, Village Fund Allocation.